Innovation, entrepreneurship, geography and growth - McCann, P.; Oxley, Leslie (2012)
This paper sets the contributions to this special issue in the context of a large and rapidly growing literature. It argues that although our understanding of the relationships between entrepreneurship, innovation, geography and economic growth is much clearer than in the past, there remains much that needs to be explored. © 2012 Blackwell Publishing Ltd.